Adoption of case-based reasoning for supporting responsive product lifecycle management - Hou, Jerrard Weizong. (2009)
In product development, many changes and decisions are made at the product design process. A responsive management system that can handle the changes occurring in the design process will shorten the product lifecycle. Case-based Reasoning can be adopted to handle and manage these changes. Case-based Reasoning is a methodology for problem solving by making use of prior experience. The problems are solved by reusing and when required, revising the solutions to similar problems solved in the past. Such a system is useful in supporting responsive lifecycle management but challenges in the development of CBR in the domain of mechanical design are present. This project proposes solutions and methodologies at different stages and components of the system to improve the Case-based Reasoning system for mechanical design. Issues regarding case retrieval efficiency and case adaptation are addressed and further recommendations were made to incorporate the use of technology in Case-based Reasoning which will enhance the practicality for commercial use. On top of that, management and maintenance techniques of verification and validation are proposed to ensure that Case-based Reasoning systems are viable and sustainable.